ANALISIS PENERAPAN MULTIMEDIA INTERAKTIF BERBANTUAN CANVA PADA MATA PELAJARAN IPAS SISWA KELAS IV SEKOLAH DASAR - Made Dian Cahyani; I Made Sedana; Putu Eka Sastrika Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Advancements in digital technology encourage teachers to utilize innovative learning media to enhance the quality of the student learning process. One such medium is interactive multimedia created with Canva, which integrates text, images, animations, video, audio, and interactive quizzes into a single learning tool. This study aims to analyze the application of Canva-based interactive multimedia regarding the topic of changes in the state of matter within the Natural and Social Sciences (IPAS) subject for fourth-grade elementary students. The study employs a qualitative approach using the library research method. Data were collected through a review of various scholarly sources—including national and international journal articles, books, conference proceedings, and education policy documents—relevant to learning multimedia, Canva, and the topic of changes in the state of matter. The data were analyzed using content analysis techniques involving collection, reduction, categorization, interpretation, and conclusion drawing. The findings indicate that the application of Canva-based interactive multimedia fosters a learning environment that is more engaging, interactive, and student-centered. The use of this medium helps students grasp concepts regarding changes in the state of matter through concrete visualizations, boosts learning motivation, strengthens engagement in the learning process, and cultivates critical thinking and problem-solving skills. Furthermore, Canva-based interactive multimedia enables teachers to present material systematically and in a manner suited to the characteristics of elementary school students. Thus, Canva-based interactive multimedia is a viable alternative learning medium for the IPAS topic of changes in the state of matter, supporting the implementation of effective and meaningful learning in elementary schools. Keywords: interactive multimedia, Canva, changes in the state of matter, IPAS, elementary school.